1997
DOI: 10.1902/jop.1997.68.9.864
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Loss One Year Following Ovariectomy in Sheep

Abstract: There is little information concerning the incidence of alveolar bone loss in estrogen‐deficient women. Ovariectomized sheep are valid models for study of the effects of estrogen deficiency on bone metabolism. The objective of this study was to compare alveolar bone loss in control (C) and ovariectomized sheep (OVX) at 3 and 12 months following surgery. OVX animals had decreased serum levels of 17‐βestradiol and increased serum levels of osteocalcin, IL‐6, and urinary levels of deoxypyridinoline which, taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
5
33
1
2
Order By: Relevance
“…20) In our experiment, after treated with genistein, the serum level of IL-1 and TNFa had significant decrease compared with OVX rats (pϽ0.01), suggesting that genistein suppress the bone resorption. However, interestingly, different from several studies, [21][22][23] the serum level of IL-6 in our experiment had no changes, suggesting that there were some differences in the mechanism between genistein and estradiol. Some researchers have reported that IL-6 exerts its effect in the initial stage of osteoclasts differentiation, while IL-1 plays its role in the later phase.…”
Section: The Effect Of Genistein On the Osteoclasts In Vitrocontrasting
confidence: 99%
“…20) In our experiment, after treated with genistein, the serum level of IL-1 and TNFa had significant decrease compared with OVX rats (pϽ0.01), suggesting that genistein suppress the bone resorption. However, interestingly, different from several studies, [21][22][23] the serum level of IL-6 in our experiment had no changes, suggesting that there were some differences in the mechanism between genistein and estradiol. Some researchers have reported that IL-6 exerts its effect in the initial stage of osteoclasts differentiation, while IL-1 plays its role in the later phase.…”
Section: The Effect Of Genistein On the Osteoclasts In Vitrocontrasting
confidence: 99%
“…In sheep, Johnson et al 26 observed significant inflammatory periodontal alterations 90 days after ovariectomy compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…The peaks identified in different studies do not always coincide; peaks from 30 to 90 days have been reported. [26][27][28][29] The use of several time intervals in this study was appropriate to reveal the duration of estrogen deficiency that showed greater influence on the bone loss caused by induced periodontitis. Previous studies did not identify this relationship because of their use of a shorter period of time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the time required to establish an accurate osteoporosis model remains inconsistent between studies. A number of previous studies (20)(21)(22)(23) have found that bone formation in sheep continues to decline between 10 weeks and 6 months after an ovariectomy, with certain studies reporting that the BMD significantly decreases 6 months after an ovariectomy (24); however, other studies have not observed these results (25).…”
Section: Discussionmentioning
confidence: 99%